2014
DOI: 10.17511/ijpr.2014.i01.03
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of tuberculosis in children up to 5 years of age

Abstract: Introduction: Tuberculosis as a disease is of great public health problem in developing countries like India. Children contribute a significant proportion of disease burden and suffer from severe form of disease, but because of difficulty in establishing an accurate diagnosis, data of disease burden in pediatric population is lacking. This study is an attempt to assess clinical profile of tuberculosis in children upto 5 years of age. Method: present study was conducted at Kamla Raja Hospital & Gajra Raja Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…It was also observed that Mantoux test was positive in only 6 (13.33%) out of 45 cases, however 50% of the CXR positive cases had positive Mantoux test. In a study of tuberculosis in children upto 5 years of age, 15 19% of patients with CNS tuberculosis had Mantoux positivity which is similar to that in our study.…”
Section: Discussionsupporting
confidence: 91%
“…It was also observed that Mantoux test was positive in only 6 (13.33%) out of 45 cases, however 50% of the CXR positive cases had positive Mantoux test. In a study of tuberculosis in children upto 5 years of age, 15 19% of patients with CNS tuberculosis had Mantoux positivity which is similar to that in our study.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, 45 children (44.1%) with suspected TB symptoms and 5 children (33%) of confirmed TB cases were under the age of 5 years, which was similar to the observations from the study conducted by Swaminathan et al [7] where 34% of confirmed TB cases were under 5 years. Slight male preponderance in the sex distribution, with a male-to-female ratio of 1.2:1, was observed in the present study which is also supported in other studies [8,9]. Despite the various issues associated with non-specific nature of symptoms, signs, and investigations and the emphasis on the various other difficulties faced in the diagnosis of pediatric TB, clinical features continue to remain the foundation of the diagnosis involved in TB [10].…”
Section: Discussionsupporting
confidence: 88%
“…In the study population, 43 children (42%) had cough in various forms, whereas Verma et al and Shrestha et al reported higher incidence of respiratory complications in 65.3% and 63.4% of cases, respectively [9,10]. Loss of appetite and fever were observed in 25% and 17.6% of the cases in the present study.…”
Section: Discussionmentioning
confidence: 45%